Advances in optoelectronics for environmental and energy sustainability - Sivanantham Nallusamy; V. Vasanthi; T. Kavinkumar; Vijayabhaskara Rao Bhaviripudi; R.V. Mangalaraja; R. Srinivasan; N. Chidhambaram; Shanmuga Sundar Dhanabalan; Perumal Asaithambi; Arun Thirumurugan (Next Energy)
Optoelectronics is advancing sustainability and energy efficiency across various industries, including renewable energy, healthcare, and environmental monitoring. This review highlights the fundamentals and mechanisms behind key optoelectronic devices such as photovoltaics, light-emitting diodes (LEDs), and sensors. It explores how advancements in photovoltaic technologies, including silicon-based, thin-film, and perovskite solar cells, are improving solar energy conversion efficiency through innovations in light absorption, charge transport, and energy band engineering. In addition, the review covers energy-efficient lighting technologies, such as LEDs, organic light-emitting diodes (OLEDs), and quantum dot-based light-emitting diodes (QLEDs), and their growing role in improving lighting systems and display technologies. Emerging trends, including flexible and wearable optoelectronic devices and integration with the Internet of Things (IoT), are also discussed, with a focus on how they contribute to more sustainable and intelligent energy solutions. Challenges like technical limitations, environmental impact, and opportunities for future research are considered, emphasizing the need for continued innovation in materials and device design. Ultimately, this article outlines the critical role of optoelectronics in shaping a sustainable, energy-efficient future across global industries, from energy and healthcare to environmental management.